Acute pericardial tamponade: The initial manifestation of systemic lupus erythematosus with Graves' hyperthyroidism. (June 2021) - Yu, Muming; Gao, Yulei; Jin, Heng; Shou, Songtao
Acute pericardial tamponade, which can cause obstructive shock, is a serious life-threatening medical emergency that can be readily reversed by timely identification and appropriate intervention. Acute pericardial tamponade can occur for a number of reasons, including idiopathic, malignancy, uremia, iatrogenic, post-myocardial infarction, infection, collagen vascular, hypothyroidism, and others. Systemic lupus erythematosus (SLE) and hyperthyroidism associated with pericardial tamponade are rarely reported. Here, we report the case of a 20-year-old female patient was final diagnosed of SLE with Graves' hyperthyroidism.